(untitled) - Cairncross, A. K. (London, 1962)
First published in 1961, this work is a compendium of essays written by esteemed economist Sir Alexander Cairncross, pertaining to the theme of economic development. A wide cross-section of factors are taken into account in this extensive collection of articles, amongst which are the importance of investment and technical progress; trade; administration and planning; and the role of education.
Keywords: Economic development; Phát triển kinh tế